Rancang Bangun Sistem Informasi Akuntansi Pengelolaan Cash Advance Purchasing Project PT. Akashi Wahana Indonesia Karawang - Komalasari, Yuli; Monika, Sintia (PROFITABILITAS, 2023)
The development of time information technology is very helpful in every activity such as in work activities in offices, it is very helpful for employees in managing the dissemination of work-related information. PT Akashi Wahana Indonesia supports technological advances based on the 2020 AOP Group Message with the theme: "Enhancing Excellence Thru Digitalization" and environmental issues related to reducing paper use, in order to use paper more effectively. Based on these two problems, every employee of PT. Akashi Wahana Indonesia needs to innovate in their respective jobs so that they can compete in the industrial era 4.0 while still paying attention to the surrounding environment. The Purchasing Project Department currently does not have a system to manage the use of cash advances related to printing, scanning and copying drawing documents outside the company. A web-based cash advance management system application was created, so that the employee concerned does not have to worry about losing invoices for using cash advance when reporting to finance at the end of the period, because every use of cash advance must be input directly into the application and upload proof of invoice. This helps reduce storage space for finance documents, facilitates monitoring of remaining cash advance balances, and minimizes paper usage when printing payment requests, printing proof of receipt of payment requests, and printing realization reports. So that the management of cash advance purchasing projects becomes more effective and efficient.